IMPORTANCE OF INDEPENDENT ASSIGNMENTS IN EDUCATIONAL ACTIVITIES (American Journal of Pedagogical and Educational Research, 2025)
This article discusses the educational and educational significance of independent work in activating students' cognitive activity. It also discusses the educational and educational significance of independent work and the types of independent work.